Optimization of Preparation Technology of Matcha Hickory Kernel and Study on Antioxidant and Lipid-lowering Activities - Fanping QIN; Ben NIU; Xiangjun FANG; Huizhi CHEN; Ruiling LIU; Hangjun CHEN; Weijie WU; Haiyan GAO (Shipin gongye ke-ji)
This study aimed to optimize the production process of matcha hickory kernel and investigate its antioxidant activity and lipid-lowering potential. Sensory scores were utilized as the evaluation criterion to identify the optimal processing technique for matcha hickory kernel via single-factor and response surface experiments. The antioxidant and lipid-lowering activities of matcha hickory kernel were assessed using various methods, including the scavenging abilities of 1,1-diphenyl-2-picrylhydrazyl (DPPH) and hydroxyl radicals, the binding capacities of sodium taurocholate and sodium glycocholate, and the impact on total cholesterol and triglyceride levels in 3T3-L1 adipocytes. The findings indicated that the most effective processing technique for matcha hickory kernel included the following parameters: White sugar content at 15%, matcha infusion concentration at 8%, baking time of 30 min, baking temperature set at 130 ℃, and a sensory score of 88.40 points. IC50 values for the scavenging abilities of DPPH and hydroxyl radicals by matcha hickory kernel were 0.50 mg/mL and 0.42 mg/mL, respectively. At a concentration of 0.10 g/mL, the binding rates of matcha hickory kernel with sodium glycocholate and sodium taurocholate were found to be 56.25% and 53.06%, respectively. At a concentration of 200 μg/mL, matcha hickory kernel demonstrated an extremely significant reduction in the levels of total cholesterol and triglycerides in 3T3-L1 adipocytes (P<0.001). The process established in this experiment is straightforward and feasible, in vitro and cellular studies have demonstrated that matcha hickory kernel possesses significant antioxidant and lipid-lowering activities.